Silicon nanostructures fabricated by Au and SiH4 co-deposition technique using hot-wire chemical vapor deposition - Chong, S.K.; Goh, B.T.; Aspanut, Z.; Muhamad, M.R.; Varghese, B.; Sow, C.H.; Dee, C.F.; Rahman, S.A. (2011)
In this study, the fabrication of Si nanostructures by Au and SiH4 co-deposition technique using hot-wire chemical vapor deposition was demonstrated. A high deposition rate of 2.7 nm/s and a high density of silicon nanostructures with a diameter of about 140 nm were obtained at T-s of 250 degrees C. An increase in T-s led to a significant reduction in the size of the nanostructures. However, coalescence on the nanostructures was observed at T-s of 400 degrees C. The Si nanostructures exhibited a highly crystalline structure, which was induced by Au crystallites. The crystallite size and crystallinity of the Si nanostructures amplified with the increase in T. The presence of nanostructures enhanced the surface roughness of the samples and clearly reduced the reflection, especially in the visible region. (C) 2011 Elsevier B.V. All rights reserved.